Exploring ESG volatility spillovers: evidence from global equity markets - De Giuli, Maria Elena; Di Persio, Luca; Mottaghi, Fatemeh; Tanda, Alessandra (Frontiers in Sustainability, 2025)
This paper investigates the volatility spillover between sustainable stocks proxied by six ESG equity indices of different geographical areas using daily returns from 2014 to 2022. We apply the Granger causality test to understand return relationships, the impulse response analysis, and the Diebold-Yilmaz spillover index. Results show that ESG equity indices are interrelated. Companies with a good ESG profile in emerging markets and clean technology are more subject to external shocks and thus more vulnerable. Understanding how risk spillover evolve and distribute across the global market in the ESG environment is key to investors and policymakers willing to foster sustainable growth.